2017
DOI: 10.14295/ras.v31i2.28663
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação físico-química das águas do processo de dessalinização de poços salobros e salinos em comunidades rurais do oeste potiguar

Abstract: Resumo: O fornecimento de água potável é o maior desafio das comunidades rurais da região semiárida do Brasil, que são caracterizadas pela escassez de recursos hídricos apropriados para consumo humano. Em uma tendência observada há alguns anos, os Governos Federal e Estadual têm buscado instalar equipamentos de dessalinização das águas salobras subterrâneas para a geração de água doce para o abastecimento de comunidades distantes dos centros urbanos. Desta forma, o objetivo deste trabalho foi avaliar a qualida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 3 publications
0
5
0
5
Order By: Relevance
“…The waters of this group present severe restriction regarding salinization due to their high EC w , whose values make practically impracticable the use of these water for irrigation. In similar works, Oliveira et al (2017) and Anders et al (2017) found that between the wells analyzed, respectively 93.60 and 90% of the wastewater samples from desalinators presented increasing or severe risk of soil salinization. The authors state that these waters are not suitable for irrigation under normal conditions and may be used on soils with good drainage, provided that adequate leaching depth is applied and salt tolerant crops are used.…”
Section: Reject Brine From Reverse Osmosismentioning
confidence: 70%
See 2 more Smart Citations
“…The waters of this group present severe restriction regarding salinization due to their high EC w , whose values make practically impracticable the use of these water for irrigation. In similar works, Oliveira et al (2017) and Anders et al (2017) found that between the wells analyzed, respectively 93.60 and 90% of the wastewater samples from desalinators presented increasing or severe risk of soil salinization. The authors state that these waters are not suitable for irrigation under normal conditions and may be used on soils with good drainage, provided that adequate leaching depth is applied and salt tolerant crops are used.…”
Section: Reject Brine From Reverse Osmosismentioning
confidence: 70%
“…Group 2 was formed by the smallest sum of squares of LSI and was composed of samples collected in the community of Boa Fé (BF1, BF2, BF3, and BF4). In this group all the samples presented a high risk of salinization, since their EC w values (6.20, 6.40, 6.20 and 5.72 dS m -1 ) (Table 4) restrict their use in irrigation, except in specific conditions of management (Terceiro Neto et al, 2013) like the mixture of water of different salinities, cultivation of salinity-tolerant plants (Dias, Ferreira, Liu, & Suarez, 2016), or the use in hydroponic farming systems (Oliveira et al, 2017).…”
Section: Brackish Water From Wellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This community and period also had the lowest value of IRQI among the samples of brackish well water (0.29). Oliveira et al (2017) classified the water of this well as with no risk of salinity and toxicity by sodium and chlorides, but with accentuated risk of infiltration problems due to its EC, compared with the SAR.…”
Section: Resultsmentioning
confidence: 99%
“…The Conama Resolution 357/2005 and the Ordinance No. 2,914 / 2011 do not assign reference values for salinity in relation to potability, but according to this Resolution, the values presented in the analysis according to the average obtained are classified as freshwater, which are classified byOliveira et al (2017) as good for irrigation practices, once they present few restrictions of use, and low risk of developing salinity problems(OLIVEIRA et al, 2017). Thus, regarding salinity, the investigated water samples are related as compatible with the most demanding uses(PESSÔA, 2013).The values obtained for total coliforms -C. Totals averaged 149.266 CFU/100mL(Table 3), with values of at least 100.0 CFU/100mL, as the rural communities of Soledade, analysis 01 (Row 63 and Column 11,Table 3); Soledade, analysis 02 (Row 64 and Column 11, fromTable 3); Soledade, analysis 04 (Row 66 and Column 11, fromTable 3); and Soledade, analysis 08 (Row 70 and Column 11, ofTable 3).…”
mentioning
confidence: 99%